2023
DOI: 10.1002/ehf2.14281
|View full text |Cite
|
Sign up to set email alerts
|

Danish phase II trial using adipose tissue derived mesenchymal stromal cells for patients with ischaemic heart failure

Abstract: Aims Patients suffering from chronic ischaemic heart failure with reduced left ventricular ejection fraction (HFrEF) have reduced quality‐of‐life, repetitive hospital admissions, and reduced life expectancy. Allogeneic cell therapy is currently investigated as a potential treatment option after initially encouraging results from clinical autologous and allogeneic trials in patients with HFrEF. We aimed to investigate the allogeneic Cardiology Stem Cell Centre Adipose tissue derived mesenchymal Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
(109 reference statements)
2
22
0
Order By: Relevance
“…A considerable number of recent clinical trials in stem cell therapy for HF have demonstrated its promise and substantially increased our understanding of the behaviors and working mechanisms of stem/progenitor cells in patients ( Table 1 ). ( Hamshere et al, 2015 ; Martino et al, 2015 ; Perin et al, 2015 ; Choudry et al, 2016 ; Noiseux et al, 2016 ; Patel et al, 2016 ; Bartolucci et al, 2017 ; Butler et al, 2017 ; Choudhury et al, 2017 ; Florea et al, 2017 ; Gwizdala et al, 2017 ; Hare et al, 2017 ; Steinhoff et al, 2017 ; Teerlink et al, 2017 ; Xiao et al, 2017 ; Bassetti et al, 2018 ; Vrtovec et al, 2018 ; Yau et al, 2019 ; Bolli et al, 2020 ; He et al, 2020 ; Makkar et al, 2020 ; Mathiasen et al, 2020 ; Ulus et al, 2020 ; Bolli et al, 2021 ; Qayyum et al, 2023a ; Qayyum et al, 2023b ; Perin et al, 2023 ) In the next phase of clinical stem cell research, it is critical to address the outcome discrepancy between preclinical and clinical studies and expand the scope of stem cell-based therapy to other forms of cardiomyopathy, such as chemotherapy- or arrhythmia-induced cardiomyopathy. Exploiting the power of AI/ML and computational tools will facilitate our understanding of the benefits and limitations of stem cell therapy and provide a systems perspective for properly applying stem cell therapeutics in the context of precision and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of recent clinical trials in stem cell therapy for HF have demonstrated its promise and substantially increased our understanding of the behaviors and working mechanisms of stem/progenitor cells in patients ( Table 1 ). ( Hamshere et al, 2015 ; Martino et al, 2015 ; Perin et al, 2015 ; Choudry et al, 2016 ; Noiseux et al, 2016 ; Patel et al, 2016 ; Bartolucci et al, 2017 ; Butler et al, 2017 ; Choudhury et al, 2017 ; Florea et al, 2017 ; Gwizdala et al, 2017 ; Hare et al, 2017 ; Steinhoff et al, 2017 ; Teerlink et al, 2017 ; Xiao et al, 2017 ; Bassetti et al, 2018 ; Vrtovec et al, 2018 ; Yau et al, 2019 ; Bolli et al, 2020 ; He et al, 2020 ; Makkar et al, 2020 ; Mathiasen et al, 2020 ; Ulus et al, 2020 ; Bolli et al, 2021 ; Qayyum et al, 2023a ; Qayyum et al, 2023b ; Perin et al, 2023 ) In the next phase of clinical stem cell research, it is critical to address the outcome discrepancy between preclinical and clinical studies and expand the scope of stem cell-based therapy to other forms of cardiomyopathy, such as chemotherapy- or arrhythmia-induced cardiomyopathy. Exploiting the power of AI/ML and computational tools will facilitate our understanding of the benefits and limitations of stem cell therapy and provide a systems perspective for properly applying stem cell therapeutics in the context of precision and personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, human clinical trials using adipose-derived MSCs for HF treatment failed to show any significant beneficial outcomes ( Qayyum et al, 2023a ; Qayyum et al, 2023b ). Yau et al reported that intramyocardially injecting allogenic BM-derived MSCs during LVAD implantation did not improve the successful weaning from LVAD, 1-year mortality, or the rate of serious adverse events ( Yau et al, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…Unlike the MyoCath catheter's stainless‐steel needle, the MyoStar catheter has a nitinol needle. Such two catheter systems have been used in the field of cardiac regeneration and repair 70–72 . Unlike the previous two catheter systems, the Helix catheter is a non‐integrated system that also allows safe transplantation of stem cells to improve myocardial contractility 73 .…”
Section: The Application Status Of Sctmentioning
confidence: 99%
“…Such two catheter systems have been used in the field of cardiac regeneration and repair. 70 , 71 , 72 Unlike the previous two catheter systems, the Helix catheter is a non‐integrated system that also allows safe transplantation of stem cells to improve myocardial contractility. 73 The C‐Cath catheter is made of nickel‐titanium alloy, which improves stem cell retention in the myocardium and ensures infusion safety and ease of use.…”
Section: The Application Status Of Sctmentioning
confidence: 99%
“…HF worsening was reported in ten trials (19,22,24,25,27,29,(31)(32)(33)(34) including 700 participants in the treatment group and 635 participants in the control group. However, one trial dominated (34) the results of this outcome, and with that trial removed, the lower risk of HF worsening in the treatment group became signi cant (RR = 0.65; 95% CI: 0.45 to 0.93, p = 0.019) (Fig.…”
Section: Heart Failure Worseningmentioning
confidence: 99%